PROTECTIVE ROLE OF A COMBINATION OF POLYHERBAL COMPOUNDS NEPHTONE AND IMMUPLUS AGAINST OXIDATIVE STRESS IN LIVER AND KIDNEY DUE TO OCHRATOXIN IN BROILERS - M K SRIKANTH,; M JEEVANA LATHA,; A GOPALA REDDY, (International Journal of Pharma and Bio Sciences, 2013)
The antioxidant potential of polyherbal compounds namely, nephtone and immuplus was assessed for therapeutic management of an experimental model of oxidative stress induced by ochratoxin, at a toxic level of 2.5 ppm in feed. A total of ninety sexed male broiler chicks (Cobb strain) of day old age were procured for the study. The chicks were randomly divided into six groups consisting of fifteen in each group. Group 1 is supplied with normal basal diet from day 1 up to 42nd day. Group 2 is administered with nephtone@ 1.2 ml / 15 birds for 1 – 2 weeks, 2.4 ml / 15 birds for 3 – 4 weeks and 4.8 ml / 15 birds for 5 – 6 weeks. Group 3 was given Immuplus@ 75mg / 15 birds for 1 – 4 weeks, 150mg / 15 birds for 5 – 6 weeks. Group 4 was administered with Ochratoxin@ 2.5 ppm in feed for 42 days. Group 5 was given Ochratoxin@ 2.5 ppm for first 28 days followed by basal diet from 29 – 42 days. Group 6 birds received ocharatoxin@ 2.5 ppm upto 42 days from day one along with a combination of nephtone and immuplus dosage as mentioned group 2 and group 3 respectively. Antioxidant defense profile (GSH-Px, GSH-R, catalase) was evaluated in blood and GSH, and TBARS was evaluated in liver. Serum parameters like ALT, BUN and total protein were evaluated as biomarkers of hepatic damage and kidney damage. Antioxidant enzyme levels and biochemical parameters were significantly altered in the ochratoxin toxic control groups. These parameters were normal in the controls (groups 1, 2, 3 and group 6 that was given immuplus therapeutically.